Research Based Learning in Indonesia’s Islamic Higher Education: A Case Study in Pragmatics Course - Farkhan , Muhammad; Tarihoran, Nafan; Supardi, Moh. (International Journal of Psychosocial Rehabilitation, 2020)
This case study aimed to know the implementation of Research-Based Learning (RBL) in Pragmatics class, its benefits, and barriers the students underwent in doing the research projects. The study took place in English Department, Univeristas Islam Negeri Syarif Hidayatullah Jakarta and Universitas Islam Sultan Maulana Hasanuddin Banten in March 2018 involving 115 students taking Pragmatics course, and two teachers handling the class as the participants. It used a questionnaire and an interview to get the students’ and teachers’ perception on the implementation of RBL in Pragmatics class; and research portfolios as primary data analyzed qualitatively using relevant concepts of RBL and autonomous learning. The study revealed that RBL encouraged the students to learn the pragmatic topics curiously exploiting their higher order thinking skills. Each student eagerly did the assignments and research project with their peers collaboratively. Therefore, the study concluded that RBL enabled the students to master content courses through learning and research activities exploiting the higher thinking skills. Moreover, they enjoyed learning because they were engaged cognitively and emotionally in doing the assignments and research projects.